Pengaruh B&C Book terhadap Kemampuan Pemecahan Masalah pada Anak Kelompok A di TK ABA 01 Surabaya - Saida, Nur; Sa'ida, Naili; Veronica, Nina; Wahono, Wahono (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2024)
Problem-solving ability in children is one of the important things that must be developed by teachers and parents so that children are accustomed to facing their problems and finding solutions to problems appropriately. However, the problem-solving ability of  Kindergarten of ‘Aisyiyah Bustanul Athfal (ABA) 01 Surabaya students is still low. This study aims to see the effect of the use of B&C Book media on problem-solving ability in Group A students at Kindergarten of ABA 01 Surabaya. This research is a pre-experimental research with One Group Pretest-Posttest Design. The subjects in the study were students in groups A1 and A2 with a total of 36 students, and the sample was taken using a simple random sampling technique with a total of 18 students. Data were collected using test and observation techniques that focused on the aspects of classifying, connecting, and comparing. Data were analyzed using the Wilcoxon match pair test. The results showed the value of Tcount = 0 and Ttable = 40 or Tcount ≤ Ttable. Thus, Ho is rejected and Ha is accepted. This means that there is a positive effect of using B&C Book on problem-solving ability in group A students at Kindergarten of ABA 01 Surabaya. It is proven by the students’ ability in classifying, connecting, and comparing has increased at the post-test.